TEKNOLOGI LAMPU TENAGA SURYA SEBAGAI SOLUSI EFISIENSI BIAYA UNTUK UMKM PENGAYU GANG NABILA ALALAK TENGAH - Anhar Khalid; Muhammad Kasim; Akbar Ela Heka; Raihan Raihan; Fitria Fitria (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
The use of electrical energy is a vital need for MSMEs, but dependence on conventional energy leads to high operational costs. As a tropical country, Indonesia has abundant solar energy potential with an average irradiation intensity of 4.80 kWh/m²/day. However, its utilization is still minimal. Solar lighting technology can be an efficient, environmentally friendly, and energy independence solution, especially in areas with limited access to electricity. The main problems are the high cost of electricity, dependence on PLN, lack of use of renewable energy technology, and limited capital and knowledge. The solutions offered include solar lighting installation, training in use and maintenance, and the provision of affordable financing schemes. The implementation method includes survey, training, installation and trial. MSME players can now benefit from the use of solar lights, which are not only cost-efficient, but also support the sustainability of their businesses by reducing their reliance on more expensive conventional energy sources. In addition, the use of renewable energy technology also supports the principles of sustainability and environmental friendliness, which are in line with the goal of developing a greener and more sustainable business.